Makhṭūṭat Butuhaning Manusya Mungguhing Sarak: Mi‘yārīyat al-Islām fī al-Manāṭiq al-Dākhilīyah bi Jawa - Agus Iswanto (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2012)
This article discusses the manuscript of Butuhaning Manusya Mungguhing Sarak as an evidence of the acceptance of Islamic texts in the cultural context of inland Java, particularly in the Sultanate of Yogyakarta, which is often considered to be more concerned with the mystical or hakikat aspects of Islam. Its analysis focuses on the way of Javanese receive the orthodox Islamic texts in the cultural context of Java and the functions of the texts in the religious life of Javanese. The existence of the Kitab Butuhaning in Yogyakarta asserts that sharī‘ah aspects have been accepted among the people in countryside Java. It also confirms that Islam in Yogyakarta seeks to balance the sharī‘ah and mystical aspects. This article argues that translations or adaptations of Arabic Islamic texts into Javanese culture and language become one of the Islamization routes in Java.DOI: 10.15408/sdi.v19i2.365